3. Jahresbericht des Instituts für Organisationsökonomik - Alexander Dilger; Stephanie Kiefer (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2013)
Der 3. Jahresbericht des vor drei Jahren gegründeten Instituts für Organisationsökonomik informiert über das Wintersemester 2012/2013 und das Sommersemester 2013. Zuerst werden das Institut, seine Professoren und Mitarbeiter vorgestellt, dann wird über die Forschung, Lehre und Weiteres des Instituts berichtet. – – The third annual report of the Institute for Organisational Economics, founded three years ago, informs about the winter semester 2012/2013 and the summer semester 2013. First the institute, its professors and employees are presented, followed by reports on research, teaching and further activities of the institute.
Keywords: 650